PENULISAN STRUKTURIERTE TEXTWIEDERGABE DALAM MATA KULIAH AUFSATZ 1 DI JURUSAN SASTRA JERMAN UNIVERSITAS NEGERI MALANG - Dewi Kartika Ardiyani (Fakultas Sastra Universitas Negeri Malang, 2010)
The purpose of this research was to figure out the effectiveness of Struk- turierte Textwiedergabe in helping students majoring in German Literature at Un- iversitas Negeri Malang improve their ability in writing the texts they read. To rec- ognize the improvement, the researcher applied classroom action research. This re- search attempted to examine and reflect on some aspects in learning process. The aspects include lecturer s performance, lecturer-student interaction, and student- student interaction. The researcher found that the teaching and learning of writing using Strukturierte Textwiedergabe can enhance the quality of the learning process and the students' achievement. Each cycle indicates similar students' achievement. The lowest achievements occurred in the second cycle, while the highest occurred in the third cycle. Generally, the teaching and learning of writing using Strukturierte Textwiedergabe can be used to improve students' writing ability